Acid Functionalization Of SBA-15 Mesoporous Catalyst For Glycerol Esterification To Monoglyceride - Hermida, Lilis (2010)
In order to exploit the glycerol stream, its transformation into monoglyceride was carried out in the present study. Monoglyceride was produced through glycerol esterification with lauric acid using acid functionalized Santa Barbara no.15 (SBA-15) mesoporous material as catalyst due to high surface area, large pore diameter and hydrothermal stability. The acid functionalized SBA-15 catalysts were synthesized by incorporating two different acid sites, i.e. propylsulfonic acid and sulphated zirconia, on the SBA-15. The SBA-15 incorporated with propylsulfonic acid (SBA-15SO3H) was prepared by refluxing a mixture of SBA-15, dry toluene, trimercaptopropyl trimethoxysilane (MPTMS) at 105 oC, followed by soxhlet extraction for 24 h to propylthiol groups. The SBA-15SO3H catalyst was obtained by oxidation of the thiol group ( -SH) to sulfonic acid form (–SO3H). Meanwhile, SBA-15 incorporated with sulfated zirconia (SBA-15SZ) was prepared by reacting SBA-15 with solution of zirconiumoxychloride and urea at 90 oC to create SBA-15ZrO2. The SBA-15SZ catalyst was obtained by reacting SBA-15ZrO2 with H2SO4 solution at 30 oC. The two types of catalysts were characterized by a number analytical techniques i.e. surface analysis, pulse chemisorption and temperature programmed desorption (TPD) of ammonia, X-ray diffraction (XRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM), energy dispersive X-ray (EDX), fourier transformed infrared (FT-IR), thermal gravimetric analysis (TGA).